Contemporary College Students' Cognitive Situation and Exploration in Green Wealth View---A Case Study of Zhejiang Yuexiu University - Xie, Yani; Xie , Yuxin; Qian , Fangbin; Luo, Ping; Huang, Zhuoling; Yu, Leyan (Pacific International Journal, 2024)
With the escalation of global environmental issues, college students, as the leading figures of the new era, play a crucial role in understanding and practicing the Green wealth view.This paper aims to explore college students' awareness of the green wealth view and analyze their roles and responsibilities in promoting the harmonious coexistence between environmental sustainability and economic prosperity. Firstly, the discussions on the green wealth view in the article are deficient,and that are mainly focus on ecological environment and resource conservation. Subsequently, through methods such as questionnaire surveys, inductive analysis, and literature research, the paper investigates college students' cognitive development regarding the green wealth view. It is found that college students have a serious lack in cognizing the concept of green wealth nowadays.Finally, the article summarizes the roles and responsibilities of college students in practicing the green wealth view, emphasizing the importance and urgency of nurturing college students with the right green wealth view. Faced with the challenges of global environmental issues, college students should embrace the mission entrusted by the times, actively participate in the creation and sharing of green wealth, and contribute to building an environmentally friendly society.